International trade consequences of climate change - Dellink, Rob (OECD Publishing, 2017)
This report provides an analysis of how climate change damages may affect international trade in the coming decades and how international trade can help limit the costs of climate change. It analyses the impacts of climate change on trade considering both direct effects on infrastructure and transport routes and the indirect economic impacts resulting from changes in endowments and production. A qualitative analysis with a literature review is used to present the direct effects of climate change. The indirect impacts of climate change damages on trade are analysed with the OECD's ENV-Linkages model, a dynamic computable general equilibrium model with global coverage and sector-specific international trade flows. By building on the analysis in the OECD (2015) report "The Economic Consequences of Climate Change", the modelling analysis presents a plausible scenario of future socioeconomic developments and climate damages, to shed light on the mechanisms at work in explaining how climate change will affect trade
Keywords: Environment; Trade